Learning with labyrinths: Neurodivergent journeying towards new concepts of care and creative pedagogy through participatory community autism research - Shaughnessy, Nicola (Critical Studies in Teaching and Learning, 2023)
This paper arises from a UK research project, Playing A/Part, which explores the identities and experiences of autistic girls through creative practices and the implications for pedagogy. Funded by the Arts and Humanities Research Council, the project was an interdisciplinary collaboration using mixed-measures and a creative and participatory approach to co-produce new knowledge about this under-represented group. The research engaged 77 girls, aged 11 to 16, in a range of educational settings: Special Educational Needs, mainstream, and selective. The focus of discussion is the emergence of the labyrinth as a creative tool for learning and well- being and the implications for care and learning in neurodivergent contexts. After contextualising the study in relation to research on autism and gender, the paper explains how labyrinths offered an appropriate ethical, aesthetic, and sensory space for the creative pedagogic practices within the research programme. The paper also considers the implications of the study for higher education in terms of teaching neurodivergent learners, and research approaches to autism.